Risk Assessment of Work Accident in Container Terminals Using the Fault Tree Analysis Method - Muhammad Arif Budiyanto; Haris Fernanda (Journal of Marine Science and Engineering, 2020)
The use of containers in the world is increasing every year in line with international trade flows. In very complex container terminal operations, the risk of work accidents is inevitable and can happen at any time. Therefore, this paper aimed to identify accidents and potential risks occurring in the container terminals. For the case study, the analysis was used the data of accidents during five years in one of the major container terminals in Indonesia. Risk assessment is carried out using the risk matrix method to get the level of risk. The risk that has the highest level is analyzed by using the Fault Tree Analysis method. From the results of the risk assessment shows the container fell to the berth when loading and unloading have the highest risk value. While the results of the Fault Tree Analysis show that traffic accidents are the biggest potential risk, which is 41.8% compared to other accidents. Moreover, human factors especially due to the negligence in operating vehicles or equipment as well as the damage of equipment were the highest common causes of accidents in the container terminal. Based on these results the contribution offered is the risk control options for terminal operators to reduce the possibility of safety failure in the container terminal.